Declining coral calcification to enhance twenty-first-century ocean carbon uptake by gigatonnes - Lester Kwiatkowski; Alban Planchat; Marc Pyolle; Olivier Torres; Nathaelle Bouttes; Adrien Comte; Laurent Bopp (Proceedings of the National Academy of Sciences, 2025)
The sensitivity of coral reefs to climate change is well established. As the oceans warm and acidify, the calcification of coral reefs declines with net calcium carbonate dissolution projected under even moderate emissions trajectories. The impact of this on the global carbon cycle is however yet to be accounted for. Here, we use a synthesis of the sensitivity of coral reef calcification to climate change, alongside reef distribution products to estimate alkalinity and dissolved inorganic carbon fluxes resulting from reductions in reef calcification. Using a global ocean biogeochemical model, we simulate the impact on ocean carbon uptake under different emissions scenarios, accounting for uncertainty in present-day calcification rates. Reductions in net coral reef carbonate production can enhance the ocean carbon sink by up to 1.25 GtCO 2 y −1 by midcentury (0.48 GtCO 2 y −1 median estimate) with cumulative ocean carbon uptake up to 13% greater by 2300 (7% median estimate). Our findings indicate that accounting for the coral reef feedback in projections will increase estimates of the remaining carbon budget associated with global warming thresholds, as well as the likelihood that net zero emissions can be achieved without negative emissions.